2017
DOI: 10.1111/xen.12342
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced effect of human mesenchymal stem cells expressing human TNF‐αR‐Fc and HO‐1 gene on porcine islet xenotransplantation in humanized mice

Abstract: Background: Porcine islet xenotransplantation is considered an attractive alternative treatment for type 1 diabetes mellitus. However, it is largely limited because of initial rejection due to Instant Blood-Mediated Inflammatory Reaction (IBMIR), oxidative stress, and inflammatory responses. Recently, soluble tumor necrosis factor-ɑ receptor type I (sTNF-αR) and heme oxygenase (HO)-1 genes (HO-1/sTNF-αR) have been shown to improve the viability and functionality of porcine islets after transplantation. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…In addition, in dilative cardiomyopathy, acute lung injury, and LPS-induced intoxication, both murine and human BM-MSCs primed by TNF or inflammatory serum secreted more sTNFR1 than the non-primed controls, which promotes disease recovery ( 119 , 120 ). In addition, human adipose-derived MSCs engineered to express sTNFR1-Fc improved the survival of porcine islets and reversed the hyperglycemia in a mouse model of streptozotocin-induced diabetes ( 140 ). sTNFR1 may act by neutralizing circulating TNF and activating mTNF-mediated reverse signaling in immune cells during diseases progression.…”
Section: Tnf Regulation Of Msc Efficacy On Autoimmune and Inflammatormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in dilative cardiomyopathy, acute lung injury, and LPS-induced intoxication, both murine and human BM-MSCs primed by TNF or inflammatory serum secreted more sTNFR1 than the non-primed controls, which promotes disease recovery ( 119 , 120 ). In addition, human adipose-derived MSCs engineered to express sTNFR1-Fc improved the survival of porcine islets and reversed the hyperglycemia in a mouse model of streptozotocin-induced diabetes ( 140 ). sTNFR1 may act by neutralizing circulating TNF and activating mTNF-mediated reverse signaling in immune cells during diseases progression.…”
Section: Tnf Regulation Of Msc Efficacy On Autoimmune and Inflammatormentioning
confidence: 99%
“…Overexpressing IL-10 in MSCs suppressed the development of graft-versus-host disease ( 160 ), and MSCs overexpressing TNFR2 treat CIA in mouse more effectively than controls ( 131 ). MSCs can also be engineered to release abundant amounts of sTNFR1 to neutralize TNF in the circulation ( 121 , 140 ). In addition, since MSCs promote activation and proliferation of Tregs, combined therapy of MSCs and Tregs further enhances the number and functions of Tregs and achieves much stronger efficacy than each alone, which has been observed in GVHD ( 161 , 162 ) and ischemic myocardium ( 163 ).…”
Section: Strategy and Perspectivementioning
confidence: 99%
“…Focusing on the pig as a donor with modification of the donor to protect the tissues or cells, Lee et al 9 have recently shown soluble tumor necrosis factorα receptor type I (s TNF-αR) and hemeoxygenase (HO)-1 genes (HO-1/s TNF-αR) can improve the viability and functionality of porcine islets after transplantation with many strategies having already been tested to prevent islet death and enhance the function of islets in improving islet engraftment.…”
Section: Advan Cing Pi G Is Le Ts For Xenotr Ans Pl Antationmentioning
confidence: 99%
“…Interestingly, in comparison with their previous studies, the islet grafts survived more than 6 months (between 225 and 727 days) in 9 of 12 transplants using the MD-3, whereas in the absence of MD-3 mA b, survival was <40 days. 9,11 Using MD-3 induction allowed for long-term survival of pig islet xenografts and successful retransplantation in this pig to monkey transplantation model. It is of note that these encouraging results were achieved following the transplantation of islets from WT pigs that had not been genetically modified.…”
Section: Advan Cing Pi G Is Le Ts For Xenotr Ans Pl Antationmentioning
confidence: 99%
“…Specifically, BLT HuMice are (1) implanted with a “Bone marrow organoid” composed of human thymus and liver tissue to support human T cell development restricted by human HLAs, and (2) injected with human CD34 + hematopoietic stem cells (HSCs; from cord blood or liver of the same donor) to allow for a broad hematopoietic lineage development . Earlier studies on porcine islet transplantation in HuMice have employed models using either peripheral blood mononuclear cells (PMBCs) or HSCs alone for humanization, and are consequently limited by the short study period due to rapid GVHD and incompleteness of human immune cell reconstitution . Tonomura et al was the first group to study porcine islet transplantation in BLT mice, although a less immunodeficient background (NOD scid ) with incomplete human hematopoietic cell engraftment was used.…”
Section: Introductionmentioning
confidence: 99%